Philological Studies: Analysis of Chinese Calligraphy at the Tjong A Fie Mansion Museum - Julina Julina; Intan Erwani; Rudiansyah Rudiansyah (Randwick International of Social Science Journal, 2020)
This article discussed the study of Chinese calligraphy texts/characters at the Tjong A Fie Mansion museum as covered in philological scholarship. The notion of philology in this paper is not limited to the root words but is broader along with the development of this science from time to time, in studying the cultural treasures of the past from the object of study which is called a manuscript. The research method was paradigmatic in order to create a form of research report that has been done. Presented starting from the descriptive, analytical and comparative stages. Utilizing the theory of philological explanation from Henri Chambert-Loir. The results of this study were the reconstruction of text/characters as the content of the manuscript which was abstract and essential, to be precise the calligraphy characters found at the main entrance, front door and back of the left-wing of the Tjong A Fie Mansion museum building.